KEMISKINAN: SEBAB STRUKTURAL DAN RESEP TEKNOKRATIS UNTUK MENGHAPUSKANNYA - Sudibyo, Bambang (Journal of Indonesian Economy and Business, 2003)
There are in Indonesian economy big discrepancies of the nominal per capita NationalIncome and its Purchasing Power Parity with a ratio of 1:5, meaning that the real economy is indeed bigger than what is reported. The very low wages and income of the lowest strata including farmers are indication that the state is being subsidized by its people. This discrepancy can and must be corrected, in stages through âstructural correctionâ.The relationship with foreign economies must not be âin their termsâ but eventually tobecome âon our termâ. National interest must be given priority in all internationalrelations, and program with IMF should be terminated as soon as possible without seriousnegative impacts to the Indonesian economy.Keywords: Economic nationalism, self-reliance.